2014
DOI: 10.1007/s13277-014-2449-0
|View full text |Cite
|
Sign up to set email alerts
|

Collagen triple helix repeat containing 1 (Cthrc1) is an independently prognostic biomarker of non-small cell lung cancers with cigarette smoke

Abstract: Collagen triple helix repeat containing 1 (Cthrc1) has been recently documented in various malignancies, but its role in non-small cell lung cancer (NSCLC) remains uncertain. In the current study, we investigated the level of Cthrc1 in NSCLC tissues by immunohistochemistry. Results revealed that Cthrc1 overexpression was significantly associated with differentiation (P=0.039), tumor-node-metastasis (TNM) stage (P=0.035), lymph node status (P=0.001), and cigarette smoke (P=0.037). Furthermore, it was shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Naturally, many other genes as MMP family [ 40 ] and Cthrc1 [ 24 ] have been demonstrated to associate with NSCLC invasion and metastasis during the ongoing researches of NSCLC. Based on bioinformatics analysis, we detected the Cthrc1 mRNA expression and found elevated expression of Cthrc1 was also associated with the occurrence of the differentiation status, TNM stage and lymph node metastases in NSCLC patients, and Pearson correlation analysis indicated that the expression of miR-30b and Cthrc1 mRNA were inversely correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, many other genes as MMP family [ 40 ] and Cthrc1 [ 24 ] have been demonstrated to associate with NSCLC invasion and metastasis during the ongoing researches of NSCLC. Based on bioinformatics analysis, we detected the Cthrc1 mRNA expression and found elevated expression of Cthrc1 was also associated with the occurrence of the differentiation status, TNM stage and lymph node metastases in NSCLC patients, and Pearson correlation analysis indicated that the expression of miR-30b and Cthrc1 mRNA were inversely correlated.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30b is a member of the miR-30 family, which plays an important regulatory role in the development of several cancers including breast cancer [ 16 ], malignant peripheral nerve sheath tumors [ 17 ], glioma [ 18 ] and lung cancer [ 19 ]. Collagen triple helix repeat containing 1 (Cthrc1) has also been associated with the development of certain cancers, including lung cancer [ 20 24 ], therefore we decided to explore a possible interaction between miR-30b and Cthrc1 and the potential significance in the invasion and metastasis of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, western blot, RT-PCR and immunofluorescence analyses results indicated that the expression of CTHRC1 in five NSCLC cell lines (NCI-H226, NCl-H23, NCl-H820, NCl-H446 and A549) was markedly stronger than that of normal human lung epithelial cells (Beas-2Bs) 11. Two independent analyses using lung cancer specimens revealed that overexpression of CTHRC1 strikingly associated with differentiation degree, clinical stage, T classification, lymph node metastasis, distant metastasis and cigarette smoke as well as with poor clinical survival time of the patients compared with patient with low CTHRC1 expression 11, 21. Furthermore, the observed results displayed that there were no significant differences between CTHRC1 and mRNA levels with different genders, ages or pathological types 22.…”
Section: Expression Profile In Several Representative Malignant Tumentioning
confidence: 97%
“…Recent research has explored the aberrant up-regulation of CTHRC1 in NSCLC 11, 21, 22, Ke al el showed that overexpression of CTHRC1 increased NSCLC proliferation, invasion and metastasis in vitro via the Wnt/β-catenin signaling pathway 11. Based on this observation, paraffin-embedded immunohistochemical analysis of CTHRC1 in NSCLC patient tissues (212/292, 72.60%) illustrated that the up-regulated levels of both mRNA and protein were evidently higher than those in the paired adjacent non-cancerous tissues (6/66, 9.09%) (p<0.001).…”
Section: Expression Profile In Several Representative Malignant Tumentioning
confidence: 99%
“…It was demonstrated that Cthrc1 is related to vascular remodeling by inhibiting collagen production and fibrogenesis, and by promoting cell migration (8). The majority of Cthrc1 studies have focused on its effects and underlying molecular mechanism, in promoting tumor cell invasion and metastasis (9)(10)(11)(12)(13)(14). In the present study, it was demonstrated that increased expression of Cthrc1 protein in gastrointestinal stromal tumor (GIST) is associated with increased microvascular density (MVD) in a tissue microarray; however, to the best of our knowledge, no previous study has demonstrated the effect of Cthrc1 in endothelial angiogenesis.…”
Section: Introductionmentioning
confidence: 99%